1996
DOI: 10.1111/j.1600-0404.1996.tb00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Regression of rnoyamoya vessels and hemodynamic changes after successful revascularization in childhood movarnova disease

Abstract: Successful revascularization improves ischemic symptoms in the pediatric patients with moyamoya disease. However, it is not clear whether the revascularization prevents future intracranial hemorrhage from the residual moyamoya vessels. The purpose of this study is to investigate perioperative morphological and hemodynamic changes in the moyamoya vessels. Four pediatric patients (age < 15 years old) with bilateral moyamoya disease were selected for this study. To quantify the number of moyamoya vessels, T1‐weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…6 Some authors have reported a benefit from revascularization in patients presenting with intracranial hemorrhage. 8,10,15,40 Although patients with nonatherosclerotic moyamoya disease and hemodynamic failure appear to benefit from surgical revascularization procedures, the optimal bypass technique has yet to be elucidated.…”
mentioning
confidence: 99%
“…6 Some authors have reported a benefit from revascularization in patients presenting with intracranial hemorrhage. 8,10,15,40 Although patients with nonatherosclerotic moyamoya disease and hemodynamic failure appear to benefit from surgical revascularization procedures, the optimal bypass technique has yet to be elucidated.…”
mentioning
confidence: 99%
“…[9][10][11] It is defined as the ratio of the mean CBF in central ROI to the mean CBF in cortical ROI. In the present study, we let hdSD 5 [average value for region I (LN)]/[average value for regions B to F (MCA)].…”
Section: Discussionmentioning
confidence: 99%
“…STA to middle cerebral artery, MCA, anastomosis) revascularization procedures resulting in subsequent neovascularization have been noted to be accompanied by a regression of the compensatory basal moyamoya network. Although this finding suggests a dynamic and controlled balance be tween sprouting and regression of blood vessels in the brain parenchyma [12,13], the natural regression of this network as the disease progresses occasionally makes this cause-and-effect relationship unclear.…”
Section: Introductionmentioning
confidence: 91%